DEC1 promotes progression of Helicobacter pylori‐positive gastric cancer by regulating Akt/NF‐κB pathway. Issue 7 (4th February 2022) - Jia, Yanfei; Liu, Yanyan; Zhu, Jingyu; Liu, Liang; Ma, Xiaoli; Liu, Duanrui; Han, Shuyi; Zhang, Lulu; Ling, Zhi‐Qiang; Wang, Yunshan
Abstract: Helicobacter pylori (H . pylori) infection plays a crucial role in the initiation and progression of gastric cancer (GC). Differentiated embryo‐chondrocyte expressed gene 1 (DEC1) is dysregulated in some cancers and may regulate cell proliferation in specific contexts. Of note, DEC1 is emerging as one of the important factors regulating cellular responses in microenvironment. However, the triggers and precise regulation mechanism for DEC1 during inflammatory carcinoma transformation of GC are unclear. In this study, we identified DEC1 was upregulated in both H . pylori ‐infected gastric tissues and GC cells. DEC1 expression was positively associated with H . pylori infection status and GC progression. DEC1‐positive expression indicated a poorer prognosis in H . pylori ‐positive GC. DEC1 was required for H . pylori ‐induced GC cells proliferation. Mechanistically, H . pylori infection significantly activated Akt/NF‐κB signal pathway and this induction depend on DEC1 expression level in GC cells. Importantly, their interaction pathway was further verified by H . pylori ‐positive gastritis mice model. Taken together, our findings identified a novel function of DEC1 in GC. H . pylori infection induce DEC1 expression, and which leading to the progression of GC through activating Akt/ NF‐κB signalling pathway. Blocking DEC1/Akt/NF‐κB, therefore, presents a promising novel therapeutic strategy for H . pylori ‐positive GC.